A PRELIMINARY ACCOUNT ON THE KHORTHA SPEECH PROSODY - Atul Aman , Niladri Sekhar Dash , Amalesh Gope (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The present study aims to explore intonational properties with special reference to focus marking system (in-situ, wide focus) in Khortha. A prosodic account of other types viz., Affirmative, Negation, Conditional and Compound and Interrogative sentences are also examined in this study. We adopted the ToBI (Tones and Break Indices) framework for transcription, annotation and analysis of the Khortha speech prosody. Khortha, an IndoAryan language is the second most spoken language after Hindi in the state of Jharkhand, India, with approximately 80 million speakers (Census reports 2011). In order to analyse the Khortha intonation patterns, we elicited a dataset containing all the intonations phrases from ten (10) native speakers (8 males, 2 females) through controlled speech experiments in a noise-free set up in the nearby villages of Giridih in Jharkhand. The first part of the questionnaire consisted of four data sets which were intended to analyse the wide focus and in-situ focus sentences, whereas the second part consisted eight affirmative, eight negative, five conditional and compound sentences and eleven other types of interrogative sentences. The conclusive analysis reveals that the subject focus element recorded the highest F0 at around 250 Hz marked as L+H*. The object focus element also recorded a relatively higher F0 at around 250 Hz, but the preceding tone marked as the lowest F0 with a continuous stretch which results in a scooped L*+H bitonal accent. The lowest pitch is marked in the left periphery of the intonation phrase in the object focus and wide focus sentences. The other significant observations regarding the pitch contour of the types of sentences are also analysed elaborately in the full paper.